Two new plant nutrient nanocomposites based on urea coated hydroxyapatite: Efficacy and plant uptake - GUNARATNE, G P; KOTTEGODA, NILWALA; MADUSANKA, NADEESH; MUNAWEERA, IMALKA; SANDARUWAN, CHANAKA; PRIYADARSHANA, W M G I; SIRIWARDHANA, ASITHA; MADHUSHANKA, B A D; RATHNAYAKE, U A; KARUNARATNE, VERANJA (The Indian Journal of Agricultural Sciences, 2016)
Macronutrient delivery to plants, particularly nitrogen, is problematic because of losses occurring during fertilization. Currently, nanotechnology is being considered as a solution to improving nutrient use efficiency. In this study, we report the synthesis and plant uptake of two plant nutrient nanocomposites based on urea coated hydroxyapatite (UHA) and potassium encapsulated into (i) a nanoclay, montmorillonite (MMT) or (ii) cavities present in Gliricidia sepium stem resulting in a wood chip containing macronutrients. Soil leaching behaviour, efficacy and plant uptake of the nutrients were tested in a pot experiment using Festuca arundinacea during a period of 60 weeks. Two nanocomposites displayed slow release behaviour particularly for nitrogen, in soil leaching tests compared to the conventional formulations. Both nanoformulations displayed efficient plant nutrient uptake highlighting the improved nutrient use efficiency. These data clearly revealed that urea fabricated into its nanoscale provide platform for development of efficient fertilizer formulations.